2015
DOI: 10.1111/jcpe.12365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of overweight/obesity on response to periodontal treatment: systematic review and a meta‐analysis

Abstract: Whereas no difference was found in clinical periodontal parameters, significant differences in inflammatory or metabolic parameters were found between overweight/obese and normal-weight patients, but existing evidence is weak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 64 publications
2
41
0
3
Order By: Relevance
“…Metaanalyses evaluating this question reported that periodontal treatment effects on oral health outcomes did not differ among obese and non‐obese groups 24 , 25 . However, periodontal treatment had a greater beneficial effect on inflammatory markers and glycemic profile in patients with diabetes and obesity compared with those with diabetes and without obesity, even when there was no effect on oral health outcomes 25 . These findings suggest that obesity may modify the effect of periodontal treatment on systemic inflammation.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Metaanalyses evaluating this question reported that periodontal treatment effects on oral health outcomes did not differ among obese and non‐obese groups 24 , 25 . However, periodontal treatment had a greater beneficial effect on inflammatory markers and glycemic profile in patients with diabetes and obesity compared with those with diabetes and without obesity, even when there was no effect on oral health outcomes 25 . These findings suggest that obesity may modify the effect of periodontal treatment on systemic inflammation.…”
mentioning
confidence: 96%
“…The effect of obesity on periodontal treatment outcomes has not been studied extensively 24–26 . Metaanalyses evaluating this question reported that periodontal treatment effects on oral health outcomes did not differ among obese and non‐obese groups 24 , 25 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, those individuals present a higher risk of chronic periodontitis 10 , 22 inducing variations among metabolic and inflammatory markers, when compared to normal-weight individuals 16 . Nevertheless, obese teenagers reported having contributed less when submitted to long orthodontic treatments with fixed appliances 14 …”
mentioning
confidence: 99%
“…The accumulation of fat was reported to lead to low-grade systemic inflammation (4). Besides, obesity and related fat accumulation might be responsible for the release of local and systemic proinflammatory cytokines and adipocytokines (including leptin, adiponectin and resistin) from adipocytes, resulting in modifications of the host response-, and playing a role in periodontal hard-and soft-tissue destruction (8)(9)(10). The studies have shown the causal relationship between the cytokines and tissue destruction (11).…”
Section: Introductionmentioning
confidence: 99%